A Flow-of-Resources Statement for Business Enterprises. - Yu, S. C. (The Accounting Review, 1969)
Abstract Recently, professors Karl Kafer and V. K. Zimmerman presented an excellently documented paper on the evolution of the funds statement in the U.S. and in Europe. Following extensive exploration, they pointed out some significant deficiencies of the funds statement. The main purpose of this article, however, is to present a different format for the construction of this flow statement. It is hoped that a structural change in this flow statement will throw some additional light on the study of flows of economic resources at the business-enterprise level. In addition to recognizing the distinction between financial and nonfinancial flows of business operations, it is important to analyze their interplay. Productive activities may be financed internally, externally, or both. A detailed presentation of the financial activities of an enterprise will show not only how additional productive resources are acquired, but will also provide a basis, in part at least, for analyzing expansion and future income flow. The conventional balance sheet and income statement are deficient in depicting financial activities of a firm and in relating theft relationship to the firm's productive activities. It must be remembered that net income is "attributable to the whole process of business activity" and that the operations involves continuous movement of productive and financial resources. The resources-flow statement should not be treated as a supplementary device. It is a basic statement in its own right. With two basic types of flows, the need for at least two flow statements is quite dear. In addition, the resources-flow statement is much more than a statement of financial flows.